Detection and genetic characterization of Tembusu virus and other flaviviruses from mosquitoes in Lao PDR - Chittaphone Vanhnollat; Somsanith Chonephetsarath; Somphavanh Somlor; Veaky Vungkyly; Tiger Soulaphy; Sopha Vongsanga; Irina V. Etobayeva; Thomas Bigot; Gary Wong; Andrew G. Letizia; Paul T. Brey; Philippe Buchy; et al. (PLoS ONE, 2026)
Background Lao People’s Democratic Republic (Lao PDR), located in Southeast Asia and known for its rich biodiversity, is part of a region recognized as a hotspot for emerging and re-emerging infectious diseases. Among flaviviruses, dengue virus (DENV) and Japanese encephalitis virus (JEV) are recognized public health threats. However, other reemerging mosquito-borne flaviviruses may also infect humans and cause diseases. Despite that, their distribution and public health impact in Lao PDR are not well understood due to limited past surveillance. Methodology Mosquitoes were collected using CDC light traps from 2021 to 2024, as part of vector and pathogen surveillance studies conducted across six provinces. A total of 2,548 female mosquitoes, representing 100 species from 11 genera, were collected and morphologically identified. Of these, 1,622 mosquitoes were pooled into 1,008 “mini pools” according to species and collection site. The pools were screened for flaviviruses by nested RT-PCR. Positive samples were further analysed by metagenomic sequencing, and coding-complete genomes were recovered and subjected to phylogenetic analysis. Primary results We recovered thirteen coding-complete genomes through metagenomic sequencing, which included one Tembusu virus (TMUV) strain (TMUV/Mos_L010) from Culex vishnui mosquitoes and 12 other insect-specific flaviviruses (ISFVs). Phylogenetic analysis placed TMUV/Mos_L010 in cluster 3, closely related to a TMUV strain known to be pathogenic to dolphins in Thailand, with more than >99% bootstrap support for amino acid homogeneity. The detected ISFVs were part of the classical insect-specific flavivirus (cISFV) lineage and were further classified into five subgroups according to their associated mosquito genera: Aedes (1), Anopheles (1), Culex (2), and Uranotaenia (1). Conclusions This study documents the first detection of TMUV in Laotian mosquitoes and extends the known distribution of cluster 3 TMUV strains. The discovery of diverse ISFVs shows the rich and underexplored virome among Laotian mosquito populations. These findings highlight the need for enhanced arbovirus surveillance and ecological research to assess zoonotic risks of spillover infections in Southeast Asia.